Pervasive Healthcare - Saranummi, N.; Wactlar, H. (Methods of Information in Medicine, 2008)
Objective: Introducing the Special Topic of Methods of Information in Medicine on pervasive healthcare, with selected papers from the Pervasive Healthcare Conference at Tampere, Finland, January 30 to February 1, 2008.Methods: Describing pervasive healthcare as field. Reporting about the content of the selected papers in this Special Topic. Developing and evaluating physiological measurement techniques, assistive care ambient notification and reminding systems, ambulatory monitoring, architectures and platforms for personalized home-health tele-monitoring, means of privacyprotecting health-sensitive information, and estab - lishing a clinical proof-of-concept methodology.Results and Conclusions: Pervasive healthcare is an emerging field with considerable technological breadth and expected strong impact for the quality and efficiency of healthcare in an aging society. However, this field is still a nascent one, with a good deal of exploratory research. There is also hypothesis-based and empirical research, which tests the assumptions or feasibility of a solution using clinical evidence, but most such trials at this time are preliminary and small. The emergence of a truly evidence-based outcomes assessment will take some time, but is in the making.
Keywords: Pervasive healthcare; pervasive computing; ubiquitous computing